Responsifitas Pemerintah Terhadap Problematika Tenaga Kerja Indonesia (TKI) - Mimin Anwartinna (Journal of Governance Innovation, 2019)
Abstract This paper wants to analyze the government's responsiveness to the problems of the Indonesian Workers, which is still leaving a sad story. Imagine, until now there are still many cases of violence, sexual harassment, labor exploitation to the death penalty for migrant workers in Saudi Arabia the other day. This is certainly a tough task for the government to pay more attention to the firmness of the law and guarantees of protection for those who have dedicated themselves to work in foreign countries. Various cases that have emerged thus far constitute a serious threat to the government if they are not immediately responsive in handling problems. Do not let the weakness of the law make an opportunity for the activities of modern slavery because it is too loose the applicable legal rules. Serious attention from the government is needed in order to be more assertive in maintaining integrity to ensure the protection of workers in foreign countries. Migrant workers should be given high appreciation because they are foreign exchange heroes for the Indonesian state. Migrant workers also contribute in supporting the progress of the nation's economy. But until now, the government is considered to be still slow in guaranteeing their protection, as evidenced by the still rampant case reports received by the government related to labor issues. In fact, the number of Indonesian Workers always increases every year. As reported by BNP2TKI's Center for Research and Development in 2013 the number of migrant workers increased by 3.6% from 2012. The increase in the number of workers has quite an effect on the stability of the country. Where more and more workers are scattered, the more the risk of problems. Therefore an evaluation of government policy is needed in this case more focused on the policy in Law number 39 of 2004 concerning the Placement and Protection of Indonesian Workers Abroad, as well as on policy derivatives in Government Regulation number 4 of 2015 related to the Implementation of Supervision of the Implementation of the Placement and Protection of Workers Indonesian Work Abroad. The policy will later be used as an evaluation reference so that the government can pay more attention to what points need to be reviewed to further emphasize the policy rules related to the protection of migrant workers' protection. Keywords: public policy, government responsiveness, Indonesian workers